PENGEMBANGAN SUPLEMEN BAHAN AJAR PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI BERBASIS BUKU CERITA BERGAMBAR PADA SISWA KELAS IV SEKOLAH DASAR - Khairunnisa Fiqri; Imam Ghozali; Vilda Ghasya; Siti Halidjah; Nany Safrianty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The use of teaching materials tailored to the needs of students plays an important role in helping them understand the application of moral values in everyday life. This study aims to produce and describe the feasibility of supplementary teaching materials for Islamic Religious Education and Ethics based on picture books for fourth-grade elementary school students. This study uses the ADDIE model. The research subjects include PAIBP teachers, librarians, and fourth-grade students at SDN 36 Pontianak Kota. Quantitative data sources come from the results of validation by subject matter experts and media experts, as well as response questionnaires from teachers, librarians, and students. Qualitative data was obtained from suggestions and input from validators, teachers, librarians, and students regarding the strengths and weaknesses of the product. Data collection was conducted through interviews and questionnaires. The validation results showed that the product obtained an average score of 96% from subject matter and media experts, categorised as highly valid. The results of the teacher and librarian response questionnaire obtained an average of 98%, and students obtained 95% with a category of very very good. Qualitatively, the validators assessed that the content of the product was in accordance with the CP, TP, ATP and characteristics of the students, and the illustrative display was attractive. The shortcomings of the product were in the clarity of the images and the provision of Latin translations, which were corrected in the final revision stage. Based on these results, it can be concluded that the teaching material supplement developed is suitable for use as a learning support medium.